Towards subpercentage uncertainty proton stopping‐power mapping via dual‐energy CT: Direct experimental validation and uncertainty analysis of a statistical iterative image reconstruction method. Issue 3 (27th January 2022) - Medrano, Maria; Liu, Ruirui; Zhao, Tianyu; Webb, Tyler; Politte, David G.; Whiting, Bruce R.; Liao, Rui; Ge, Tao; Porras‐Chaverri, Mariela A.; O'Sullivan, Joseph A.; Williamson, Jeffrey F.
Abstract: Purpose: To assess the potential of a joint dual‐energy computerized tomography (CT) reconstruction process (statistical image reconstruction method built on a basis vector model (JSIR‐BVM)) implemented on a 16‐slice commercial CT scanner to measure high spatial resolution stopping‐power ratio (SPR) maps with uncertainties of less than 1%. Methods: JSIR‐BVM was used to reconstruct images of effective electron density and mean excitation energy from dual‐energy CT (DECT) sinograms for 10 high‐purity samples of known density and atomic composition inserted into head and body phantoms. The measured DECT data consisted of 90 and 140 kVp axial sinograms serially acquired on a Philips Brilliance Big Bore CT scanner without beam‐hardening corrections. The corresponding SPRs were subsequently measured directly via ion chamber measurements on a MEVION S250 superconducting synchrocyclotron and evaluated theoretically from the known sample compositions and densities. Deviations of JSIR‐BVM SPR values from their theoretically calculated and directly measured ground‐truth values were evaluated for our JSIR‐BVM method and our implementation of the Hünemohr–Saito (H‐S) DECT image‐domain decomposition technique for SPR imaging. A thorough uncertainty analysis was then performed for five different scenarios (comparison of JSIR‐BVM stopping‐power ratio/stopping power (SPR/SP) to International Commission on Radiation Measurements and Units benchmarks; comparison of JSIR‐BVM SPR to measured benchmarks; and uncertainties in JSIR‐BVM SPR/SP maps for patients of unknown composition) per the Joint Committee for Guides in Metrology and the Guide to Expression of Uncertainty in Measurement, including the impact of uncertainties in measured photon spectra, sample composition and density, photon cross section and I‐value models, and random measurement uncertainty. Estimated SPR uncertainty for three main tissue groups in patients of unknown composition and the weighted proportion of each tissue type for three proton treatment sites were then used to derive a composite range uncertainty for our method. Results: Mean JSIR‐BVM SPR estimates deviated by less than 1% from their theoretical and directly measured ground‐truth values for most inserts and phantom geometries except for high‐density Delrin and Teflon samples with SPR error relative to proton measurements of 1.1% and −1.0% (head phantom) and 1.1% and −1.1% (body phantom). The overall root‐mean‐square (RMS) deviations over all samples were 0.39% and 0.52% (head phantom) and 0.43% and 0.57% (body phantom) relative to theoretical and directly measured ground‐truth SPRs, respectively. The corresponding RMS (maximum) errors for the image‐domain decomposition method were 2.68% and 2.73% (4.68% and 4.99%) for the head phantom and 0.71% and 0.87% (1.37% and 1.66%) for the body phantom. Compared to H‐S SPR maps, JSIR‐BVM yielded 30% sharper and twofold sharper images for soft tissues and bone‐like surrogates, respectively, while reducing noise by factors of 6 and 3, respectively. The uncertainty (coverage factor k = 1) of the DECT‐to‐benchmark values comparison ranged from 0.5% to 1.5% and is dominated by scanning‐beam photon‐spectra uncertainties. An analysis of the SPR uncertainty for patients of unknown composition showed a JSIR‐BVM uncertainty of 0.65%, 1.21%, and 0.77% for soft‐, lung‐, and bony‐tissue groups which led to a composite range uncertainty of 0.6–0.9%. Conclusions: Observed JSIR‐BVM SPR estimation errors were all less than 50% of the estimated k = 1 total uncertainty of our benchmarking experiment, demonstrating that JSIR‐BVM high spatial resolution, low‐noise SPR mapping is feasible and is robust to variations in the geometry of the scanned object. In contrast, the much larger H‐S SPR estimation errors are dominated by imaging noise and residual beam‐hardening artifacts. While the uncertainties characteristic of our current JSIR‐BVM implementation can be as large as 1.5%, achieving < 1% total uncertainty is feasible by improving the accuracy of scanner‐specific scatter‐profile and photon‐spectrum estimates. With its robustness to beam‐hardening artifact, image noise, and variations in phantom size and geometry, JSIR‐BVM has the potential to achieve high spatial‐resolution SPR mapping with subpercentage accuracy and estimated uncertainty in the clinical setting.